Relaksasi Progresif terhadap Intensitas Nyeri Post Operasi BPH (Benigna Prostat Hyperplasia) - Aprina Aprina; Noven Ilham Yowanda; Sunarsih Sunarsih (Politeknik Kesehatan Tanjung Karang, 2017)
Pain is one of the most common complaints in patients after experiencing a surgery. Surgery is a biphasic event against the human body that implies pain management. In post-surgery patients feel severe pain and 75% of patients have unpleasant experiences due to inadequate pain management.Based on the results of activity reports in Dr. Hi. Abdul Moeloek Public Hospital in Lampung Province in July-December 2016 obtained data operation BPH as many as 51 inhabitants. The objective of this research was to find out the effect of progressive relaxation to an intensity of pain for BPH (Benigna Prostate Hyperplasia) post-surgery patient. This was a quasi-experiment research by using one group pretest and posttest design. 20 respondent samples were taken by using accidental sampling. Data were collected by using observation sheet and analyzed by using univariate and bivariate analyses with Wilcoxon sign test. The results showed that the mean value of pain before the progressive relaxation therapy equal to 5.20 with standard deviation 0.834. While the mean value of pain scale after it was 3.60 with standard deviation 0.681. Analysis with Wilcoxon sign test derived p-value 0.000 (ρ-value 0.000 < α 0.05), and the conclusion there was a significant effect the mean value of pain in the post-surgery patient’s BPH (Benigna Prostate Hyperplasia) after progressive relaxation therapy. The researcher expects that the progressive relaxation therapy can be used by more operational methods.